1995
DOI: 10.1108/09684889510087809
|View full text |Cite
|
Sign up to set email alerts
|

A rose by any other name: TQM in higher education

Abstract: Understanding quality and its relevance to higher educationThe impact of quality on reputation is nowhere more marked than in higher education. Indeed, reputation is the most important -and marketable -good of every higher education institution (HEI): "Ours is a reputational business -an enterprise whose revenues are driven by the perception and substance of its reputation for quality and the skill with which that reputation is marketed" (Tulane University, 1989).Since no one has yet satisfactorily defined or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…However, literature has indicated that educational institutions have been lagging behind other organizations in their Total Quality culture (TQ culture; Bolton, 1995;Singh et al, 2008;Sirvanci, 2004). An organization with a total quality culture is an organization that has a clear set of values and beliefs that foster total quality behavior.…”
Section: The Importance Of Tqm As a Strategic Issue For Qatari Educatmentioning
confidence: 98%
See 3 more Smart Citations
“…However, literature has indicated that educational institutions have been lagging behind other organizations in their Total Quality culture (TQ culture; Bolton, 1995;Singh et al, 2008;Sirvanci, 2004). An organization with a total quality culture is an organization that has a clear set of values and beliefs that foster total quality behavior.…”
Section: The Importance Of Tqm As a Strategic Issue For Qatari Educatmentioning
confidence: 98%
“…Managers have the power and authority to determine the organizational strategy, systems, policies, and operating procedures. If management does not understand the total quality concept, then their influences on the behavior of employees and the level of support for quality issues and improvements programs may be detrimental (Atkinson, 1990;Bolton, 1995;Sirvanci, 2004). When a cross tabulation was constructed and respondents were classified into institutional levels (Table 5), it was further established that respondents from the primary institutions seem to have implemented or planned TQM better (about 43% responded "Yes" while 36% responded "No") and showed a higher percentage or better awareness and understanding of TQM in terms of knowing the purpose of TQM (64% responding "Yes" and 7% "No") compared to the secondary (40% responding "Yes" and 27% responding "No") and tertiary institutions (46% responding "Yes" and 27% responding "No").…”
Section: Background Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…These include difficulty measuring the educational product, a wide variety of viewpoints and the focus on seeking funding for university programs. Additional issues from an earlier study include unclear definition of the customer, inability to measure educational products, focus on individual work and lack of commitment to change (Bolton, 1995).…”
mentioning
confidence: 98%